State of Art of Landfill Leachate Treatment: Literature Review and Critical Evaluation - Lippi, Marcelo; Ley, Michelle Bellas Romariz Gaudie; Mendez, Gabriel Pinna; Cardoso Junior, Ricardo Abranches Felix (Ciência e Natura, 2018)
Population growth, especially in urban areas, combined with modern levels of social consumption, contribute for a significant increase of waste production. Among the environmental impacts resulting from the operation of landfills, the generation of leachate is certainly one of the most significant and most difficult to control. The composition of leachate is complex and varied; it contains physicochemical and biological characteristics that are aggressive to the soil, water resources, fauna and flora. The technical and operational difficulties to handle it are challenges for waste managers. There are several methods to treat leachate which are widely debated in the literature, each having advantages and disadvantages. The present paper has the objective of carrying out a bibliographical review of leachate treatment from landfills, addressing the main technologies, as well as discussing their applications, advantages, disadvantages and uncertainties. According to what was studied, the technologies that have been found to have the best practical results and, in general, reach the parameters for treated effluent provided for environmental legislations, are those that use filtering membranes. However, one of the major disadvantages of these processes is the generation of a concentrate, which is normally recirculated in the landfill itself.